Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00113-014-2659-3
|View full text |Cite
|
Sign up to set email alerts
|

Toxic-shock-Syndrom nach offener Sprunggelenkverletzung

Abstract: The treatment of open fractures is a challenge for the attending surgeon. Depending on the severity, the risk of infection rises up to 50%. Local infection up to the point of sepsis can develop in spite of surgical and antimicrobial therapy. The present case demonstrates the case of an 18-year-old man who developed toxic shock syndrome (TSS) after an open ankle fracture. This potentially life-threating syndrome usually presents with the main symptoms of fever, hypotension and exanthema and is caused by toxins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…A total of 19.6% of all S. aureus isolates in our study were positive for tst gene, a much higher frequency than those reported by other researchers (0.0% to 3.5%) Li et al, 2018;Marek, Pyzik, Stępień-Pyśniak, Urban-Chmiel, & Nowaczek, 2018;Sallam, Abd-Elghany, Elhadidy, & Tamura, 2015). The presence of tst gene in high frequency of S. aureus poses a zoonotic risk to chicken handlers as previous works confirmed that TSST-producing S. aureus had caused human diseases (Klüter et al, 2015;Sharma et al, 2018). This is the first documentation of S. aureus strains with tst positive genes from animal, food or human sources in South Africa.…”
Section: Discussionsupporting
confidence: 50%
“…A total of 19.6% of all S. aureus isolates in our study were positive for tst gene, a much higher frequency than those reported by other researchers (0.0% to 3.5%) Li et al, 2018;Marek, Pyzik, Stępień-Pyśniak, Urban-Chmiel, & Nowaczek, 2018;Sallam, Abd-Elghany, Elhadidy, & Tamura, 2015). The presence of tst gene in high frequency of S. aureus poses a zoonotic risk to chicken handlers as previous works confirmed that TSST-producing S. aureus had caused human diseases (Klüter et al, 2015;Sharma et al, 2018). This is the first documentation of S. aureus strains with tst positive genes from animal, food or human sources in South Africa.…”
Section: Discussionsupporting
confidence: 50%